Improving the technology of working with gifted students - Munavvarxon Muxammadaliyeva Maxmudjon qizi (Zien Journals, 2022)
In this article, several views on the importance of the personal activity of a gifted child, as well as the psychological mechanisms of self-development of a person underlying the formation and implementation of individual talent, have been put forward
Keywords: Talent; practice-oriented system; high skills; individual training